Association between the neutrophil-to-lymphocyte ratio and risk of in-hospital heart failure and arrhythmia in patients with acute myocardial infarction - Zhang, Jia-li; Yang, Rui; Zhu, Yi; Shao, Yan; Ji, Yuan; Wang, Fang-fang (Frontiers in Cardiovascular Medicine, 2023)
Background: This study was to probe into the relationship between the neutrophil-to-lymphocyte ratio (NLR) and both in-hospital and long-term heart failure risk in patients with acute myocardial infarction (AMI). Methods: 990 patients with AMI, including 386 with non-ST-segment elevation myocardial infarction (NSTEMI) and 604 with segment elevation myocardial infarction (STEMI) were recruited between January 2019 and March 2022. The in-hospital acute heart failure (AHF) and arrhythmia events were recorded. Results: The NLR was significantly greater in the AHF group in STEMI and NSTEMI patients, with a higher frequency of arrhythmia in comparison to the non-AHF group. A high NLR was related to a high level of myocardial injury markers, accompanied with more AHF and arrhythmia events. Multivariate logistic regression analyses revealed that high NLR is independently linked with increased in-hospital AHF and arrhythmia risk. Receiver operating characteristic curve analyses revealed that the prognostic value of NLR for in-hospital AHF was 0.704 in STEMI patients and 0.766 in NSTEMI patients. However, during a median follow-up of 28 months with 32 heart failure patients, there was no significant difference between the low NLR group (n=18) and the high NLR group (n=14). Further analysis showed that the two groups did not significantly differ in the occurrence of heart failure within 12 months of discharge. Conclusion: Our results indicate that NLR is an independent risk factor of in-hospital AHF in AMI patients. However, NLR has no value in predicting long-term heart failure.